Midterm Exam - Renzulli, L. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The goal of the exam is for you to show mastery of the organizational literature presented in the course thus far. I expect that you will use the material from this class and do not expect outside research to be able to answer the following questions. I will be looking for answers that show comprehension, synthesis, and evaluation of the works and theories. You should use examples from the empirical works to help given an appraisal of the theories.